STUDIES ON THE PATHOGENESIS OF ACUTE INFLAMMATION : III. THE FAILURE OF ANTICOAGULANTS TO PREVENT THE LEUCOCYTIC STICKING REACTION AND THE FORMATION OF SMALL THROMBI IN RABBIT EAR CHAMBERS DAMAGED BY HEAT - Allison, Fred (The Rockefeller University Press, 1961)
Vigorous anticoagulation with heparin sodium and sodium warfarin singly and in combination did not prevent the margination and endothelial sticking reaction of leucocytes in rabbit ear chambers damaged by heat. The general inflammatory reaction observed in this preparation was similarly uninfluenced by the anticoagulants. An unexpected finding after administration of heparin was the enhanced formation of platelet and fibrin-like thrombi within damaged ear chambers. Sodium warfarin did not induce or prevent this heparin effect. Production of these heparin-associated thrombi was minimized in animals subjected to defibrinogenation in vivo whereas leucocytic sticking was not modified. Although defibrinogenation was not absolute, these experiments represent additional proof that the sticking of white blood cells to vascular endothelium is not causally related to the fibrinogen-fibrin system.